Kaempferol prevents aseptic loosening via enhance the Wnt/β-catenin signaling pathway in vitro and in vivo - Qiu, Wenkui; Li, Zhenghui; Su, Zhenyan; Cao, Lichao; Li, Lei; Chen, Xi; Zhang, Wanhong; Li, Yanqing (European Journal of Medical Research, 2023)
Kaempferol has demonstrated notable positive effects on the osteogenic differentiation of mesenchymal stem cells (MSC) and osteoblasts. A substantial body of research has emphasized the role of dislodged titanium particles in aseptic loosening following joint replacement surgery. This study predominantly investigates the suppressive influence of Kaempferol on osteolysis induced by titanium (Ti) alloy particles. In vitro investigations disclosed that Kaempferol effectively enhanced mineralization and alkaline phosphatase (ALP) activity in bone-marrow mesenchymal stem cells exposed to Ti particles. In addition, we conducted a comprehensive analysis of osteogenic differentiation microarray data_sets (GSE37676, GSE79814, and GSE114474) to identify differentially expressed genes. Significantly, Kaempferol upregulated the expression of critical osteogenic markers, including Runt-related transcription factor 2 (Runx2), osteocalcin (OCN), osterix/Sp-7, and β-catenin. In vivo experiments, including H&E staining and Immunohistochemistry, provided compelling evidence that Kaempferol exerted a robust inhibitory effect on periprosthetic osteolysis in mice, with particularly pronounced results at higher doses. Moreover, it elevated the expression levels of osteogenic factors and Wnt/β-catenin signaling components. These findings collectively indicate that Kaempferol mitigates the hindrance to osteogenesis posed by titanium particles by activating the Runx2 and Wnt/β-catenin signaling pathways. This research lays a solid foundation for the prospective utilization of Kaempferol in the management of aseptic loosening following arthroplasty, offering promising therapeutic potential.
CRIS-Team Scopus Importer:2023-11-17